PENGEMBANGAN E-MODULE BERBASIS KONTEKSTUAL MENGGUNAKAN APLIKASI EXE LEARNING PADA MATERI USAHA DAN ENERGI DI SMA KELAS X - Lisbet Sihombing; Nur Islami; Zuhdi Maaruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problems faced today by both teachers and students in learning physics include: the lack of variations in the teacher's teaching methods in delivering material to students, the low motivation of students to learn physics and the lack of media used by teachers in delivering the material. From the problems above, the researchers tried to provide a solution, namely by developing contextual-based teaching materials/media using the exe learning application. Exe learning application technology can be used to design innovative and interesting physics learning media. This contextual-based learning media presents business and energy materials with animations that are more interesting and fun to learn. The form of research carried out is development research with the term Research And Development (R&D) and the model used is ADDIE. This development is guided by high school students who can already think contextually or connect the material studied with students' daily lives. So they catch the lesson faster. The validation results from the validator show that contextual-based learning media using exe learning applications on work and energy theory in class X SMA is valid (teaching materials are as expected).Key Words: Contextual, Exe learning.